2022
DOI: 10.3390/w14030462
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupled Precipitation and Water Availability: The Case Study of Municipality of Sfakia, Crete, Greece

Abstract: Sfakia is a mountainous municipality located in the southwestern area of the island of Crete, including the southern part of the Lefka Ori mountain, with an elevation ranging from sea level to over 2400 m. The mountainous massif mainly consists of carbonate rocks and intense karstic phenomena can be observed. The part of the area exceeding over the elevation of 600 m is characterized by high amounts of precipitation (1500 mm). Despite this high precipitation, the water availability in the area is low. This wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…In this Special Issue, the study of Tzanakakis et al [16] highlights the critical role of geomorphology and the geological setting of a specific area on the island of Crete, Greece, in water availability. It is shown that, despite the high precipitation, the area is suffering from low water availability due to hydrological basin characteristics (karsts) that redirect water away, favoring precipitation loss through runoff.…”
Section: Rethinking Climate Climate Change and Its Relationship With ...mentioning
confidence: 99%
“…In this Special Issue, the study of Tzanakakis et al [16] highlights the critical role of geomorphology and the geological setting of a specific area on the island of Crete, Greece, in water availability. It is shown that, despite the high precipitation, the area is suffering from low water availability due to hydrological basin characteristics (karsts) that redirect water away, favoring precipitation loss through runoff.…”
Section: Rethinking Climate Climate Change and Its Relationship With ...mentioning
confidence: 99%